Penerapan Model Pembelajaran Berbasis Masalah untuk Meningkatkan Kemampuan Berpikir Kritis dan Disposisi Matematis Siswa - Husnidar Husnidar; M. Ikhsan; Syamsul Rizal (Didaktik Matematika, 2014)
The purpose of this study was to determine the improvement of critical thinking skills and students mathematical dispositions, as well as the interaction between learning factors and grouping of students to the critical thinking skills and the improvement of student mathematical dispositions. This study is an experimental study with a quantitative approach that describes an increase in critical thinking skills and dispositions of students overall mathematical and grouping students. The population inthis study were students of SMP Negeri 3 Peusangan, where in the sample is a class VIII student as much as 2 classes with 47 students enrolled. The sampling technique is done by simple random sampling design with pretest-posttest control group. Based on the results of the study concluded that the improvement of students critical thinking skills mathematical significantly higher in grade PBM than conventional class as a whole with a value of t = 4.373. However, the grouping of students simply an increase in the high group and medle group only, namely the value of t = 4.064 and t = 2,554. The study also concluded that there was an interaction between learning factors and grouping of students to the mathematical ability of students to think critically. In addition, the results of a study of students mathematical dispositions that get higher problem-based learning than students who received conventional teaching overall with a value of t= 4.214. While the grouping of students is only an increase in the high group with a value of t = 2.428 and the low group with a value of t = 3.439. But in the process of interaction, there is no interaction between factors of learning and grouping of student to an increase students mathematical dispositions.